Association of single nucleotide polymorphism in the MBL1 gene with mastitis in Vrindavani crossbred cattle - ASAF V N, MUHASIN; KUMAR, AMOD; PANIGRAHI, MANJIT; DEWANGAN, PRASHANT; GAUR, G K; BHUSHAN, BHARAT (The Indian Journal of Animal Sciences, 2014)
Mannose-binding lectin 1 (MBL1) is one of the most important constituent of the innate immune system. Several studies have reported that MBL1 gene polymorphisms were associated with milk somatic cell score in cattle. In the present study, the animals were grouped into mastitis negative and positive animals on the basis of California mastitis test (CMT) and somatic cell count (SCC). Genomic DNA was isolated from blood samples and allele specific PCR was used to genotype the SNP, rs110326717 (g.2651G>A) under study. The SNP was found to be polymorphic in both the affected as well as unaffected groups of cows but no significant association between the genotypes with the clinical mastitis was obtained. Although there is lack of association, further studies have to be undertaken in large population to validate the impact of rs110326717 and the host response to mastitis.